A Chesapeake Shores Christmas - Woods, Sherryl (Woods, Sherryl. Chesapeake Shores novel., 2010)
Mick and Megan O'Brien finally make plans to walk down the aisle, but not everyone is happy about the upcoming wedding as they are. There's a good chance complications will keep this reunited couple from ever saying "I do."